Co-whites : how and why white women "betrayed" the struggle for racial equality in the United States - Aniagolu, Emeka (University Press of America, 2011)
"Aniagolu examines the dynamics of race and gender in the history of the United States, concluding that white American women collaborated with white American men as 'Co-Whites' or co-partners in the management and maintenance of white supremacy in the United States."--Provided by publisher